2017
DOI: 10.1186/s12983-017-0214-0
|View full text |Cite|
|
Sign up to set email alerts
|

Getting fat or getting help? How female mammals cope with energetic constraints on reproduction

Abstract: BackgroundFat deposits enable a female mammal to bear the energy costs of offspring production and thus greatly influence her reproductive success. However, increasing locomotor costs and reduced agility counterbalance the fitness benefits of storing body fat. In species where costs of reproduction are distributed over other individuals such as fathers or non-breeding group members, reproductive females might therefore benefit from storing less energy in the form of body fat.ResultsUsing a phylogenetic compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 111 publications
1
41
0
1
Order By: Relevance
“…Sex‐specific differences related to the consequences of body condition variation suggest that females and males are differentially affected. Motherhood is a significant influence in the depletion of a female's reserves for mammals (Heldstab, Schaik, & Isler, ). Our data showed a seasonal periodic decrease in SMI at the end of the wet season just after breeding.…”
Section: Discussionmentioning
confidence: 99%
“…Sex‐specific differences related to the consequences of body condition variation suggest that females and males are differentially affected. Motherhood is a significant influence in the depletion of a female's reserves for mammals (Heldstab, Schaik, & Isler, ). Our data showed a seasonal periodic decrease in SMI at the end of the wet season just after breeding.…”
Section: Discussionmentioning
confidence: 99%
“…The very conservative reproductive 507 investment may reflect the need to deal with fluctuating food abundance (Knott, 2001), 508 including multiple periods of food scarcity during the years of extended lactational effort (van 509 Noordwijk et al, 2013). The arboreal lifestyle limits opportunities for fat storage to buffer 510 fluctuations in food intake (Heldstab et al, 2017), which further contributes to the risk of 511 maternal energy depletion in orangutans (Knott, 2001, Knott et al, 2009. The slowdown also 512 enables the hypometabolism found in orangutans (Pontzer et al, 2016).…”
Section: Causes Of Mortalitymentioning
confidence: 99%
“…Another factor influencing fat storage in reproduction is whether the female provides the effort alone, or has helpers. A phylogenetic analysis of 87 mammal species showed that if females have helpers, the amount of stored fat reserves called upon for reproduction is reduced (Heldstab et al, 2017).…”
Section: Introductionmentioning
confidence: 99%